2021
DOI: 10.1140/epjc/s10052-021-09152-2
|View full text |Cite
|
Sign up to set email alerts
|

Search for the singlet vector-like lepton at future $$e^+ e^-$$ colliders

Abstract: Searching for the new particles beyond the standard model (SM) is an important way to probe new physics beyond the SM. In one class of new particles there are nonchiral color singlet fermions that couple to the SM leptons, that is vector-like leptons (VLLs), which have been widely concerned in experiment and theory. The existing literature shows that the singlet VLLs suffer from a big difficult challenge for discovery at future proton-proton colliders. In this paper, we study the prospects of searching for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Fig- ure18 shows the VLL pair-production cross-sections as a function of M τ for e + e − collisions at √ s = 1000 GeV in the Singlet VLL model and √ s = 3000 GeV in the Doublet VLL model for various choices of the beam polarizations. One sensitivity study for the ILC and CLIC, performed in a fully leptonic final state, suggests that almost the entire accessible range of M τ for each collider energy could be excluded with 15 fb −1 (ILC 500 GeV), 23 fb −1 (ILC 1.0 GeV), and 200 fb −1 (CLIC 1.5 TeV) [316]. In fully hadronic final states the required luminosities decrease considerably, offering strong promise for discovery of a Singlet VLL.…”
Section: Charged Leptonsmentioning
confidence: 99%
“…Fig- ure18 shows the VLL pair-production cross-sections as a function of M τ for e + e − collisions at √ s = 1000 GeV in the Singlet VLL model and √ s = 3000 GeV in the Doublet VLL model for various choices of the beam polarizations. One sensitivity study for the ILC and CLIC, performed in a fully leptonic final state, suggests that almost the entire accessible range of M τ for each collider energy could be excluded with 15 fb −1 (ILC 500 GeV), 23 fb −1 (ILC 1.0 GeV), and 200 fb −1 (CLIC 1.5 TeV) [316]. In fully hadronic final states the required luminosities decrease considerably, offering strong promise for discovery of a Singlet VLL.…”
Section: Charged Leptonsmentioning
confidence: 99%
“…However, the contribution in the total cross-section is not so large due to destructive interference between the s-ans the t-channel diagrams. The effect of the polarization of the electron and positron beam has been discussed in detail in Ref: [60], and we have followed the exact same polarization of the e + and e − beam which leads to maximum -60% left right asymmetry (A LR )…”
Section: Signalmentioning
confidence: 99%
“…Literature [7] studies the topic of finding VLL in the half-photon channel of the high-energy e~+e~-collider, based on the different decay modes of the electroweak standard boson, the signal is divided into two modes, A and B, and detailed detector simulations are carried out respectively, and it is found that the A mode is more capable of ruling out and discovering the VLL. The construction of new particles that extend beyond the Standard Model is a significant way to explore new physics beyond the Standard Model, according to literature [8].…”
Section: Introductionmentioning
confidence: 99%